Mapping Cross-Border Financial Linkages : A Supporting Case for Global Financial Safety Nets. (Policy Papers; Policy Paper ;, 2011)
This paper maps cross-border financial linkages and identifies factors that drive them, contributing to the discussion on the appropriate design of a global financial safety net (GFSN). It builds on previous staff work and complements the findings of the companion paper on theaAnalytics of Systemic Crises and the Role of Global Financial Safety Nets. This paper notes the growing roles of financial linkages and complexity in injecting latent instability into the global financial system, underscoring the value of a GFSN design that is effective in forestalling the risk that a localized liquidity shock propagates through the global financial network turning into a large-scale systemic crisis.